Reconnaissance for Uranium in the Lost River Area, Seward Peninsula, Alaska - White, Max Gregg; West, Walter S. (United States. Government Printing Office., 1952)
Abstract: Reconnaissance for uranium in the Lost River area, Seward Peninsula, Alaska, during the 1951 field season revealed the presence of minor amounts of radioactive material in mineralized portions of rhyolitic dikes and in a small iron-enriched zone in limestone. The dikes contain as much as 0.01 percent equivalent uranium locally and average 00005 percent equivalent uranium. The radioactive material occurs as a secondary hematitic coating of the dike rock. The iron-enriched zone has an average content of about 0.06 percent equivalent uranium with the radioactive material occuring in limonite, hematite, goethite, and mimetite. The radioactivity of these minerals is due to the presence of uranium as an impurity. No uranium deposits of economic importance were found.